2017
DOI: 10.1155/2017/9570129
|View full text |Cite
|
Sign up to set email alerts
|

TNF Tolerance in Monocytes and Macrophages: Characteristics and Molecular Mechanisms

Abstract: Tumor necrosis factor (TNF) tolerance in monocytes and macrophages means that preexposure to TNF reduces the sensitivity in these cells to a subsequent restimulation with this cytokine. Differential effects arise following preincubation with both low and high doses of TNF resulting in absolute as well as induction tolerance affecting specific immunologically relevant gene sets. In this review article, we summarize the relevance of TNF tolerance in vivo and the molecular mechanisms underlying these forms of tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 65 publications
0
34
0
Order By: Relevance
“…While the endotoxin tolerance is generally mediated by TLR4, other microbial products can stimulate receptors such as TLR2 (116) or TNF receptor (117) to induce crosstolerance. TNF selectively diminished cytokine production in response to subsequent endotoxin challenge (118). A low dose of TNF protected mice from the lethal effects of subsequent challenge with a high dose of LPS (117).…”
Section: Immune Tolerance In Perspective To Explain Refractory State mentioning
confidence: 99%
See 1 more Smart Citation
“…While the endotoxin tolerance is generally mediated by TLR4, other microbial products can stimulate receptors such as TLR2 (116) or TNF receptor (117) to induce crosstolerance. TNF selectively diminished cytokine production in response to subsequent endotoxin challenge (118). A low dose of TNF protected mice from the lethal effects of subsequent challenge with a high dose of LPS (117).…”
Section: Immune Tolerance In Perspective To Explain Refractory State mentioning
confidence: 99%
“…In CTL JD(+) macrophages, TNF upregulation was maintained compared to JD(-) CTLs. Genes that are critical for the induction of tolerance in human monocytes such as TNF and TNFAIP3 (encoding A20 protein) (118,119) were also more expressed in control JD(+) macrophages than in CTL JD(-) macrophages. Our results suggest a phenomenon similar to the crosstolerance in these JD(+) macrophages through a mechanism that requires further investigation.…”
Section: Immune Tolerance In Perspective To Explain Refractory State mentioning
confidence: 99%
“…In this context, the term tolerance describes a physiological phenomenon in which a pretreatment of organisms or specific cell types (e.g., monocyte/macrophages or hepatocytes) with a specific activating stimulus over a certain time leads to the resistance towards further stimulation with the same (or, in the case of cross-tolerance, another) substance. In its pure form, tolerance is mostly expressed as TNF, LPS, or TNF/LPS (cross-)tolerance [286] and reflected by the repression of immunologically relevant genes, such as IL-8 [287] or Il-6 [288]. TNF tolerance may occur in two forms, i.e., absolute tolerance (in which gene expression is blocked) and induction tolerance (in which gene expression is not further inducible).…”
Section: Inhibition Of Gsk3 and The Perpetuation Of Inflammationmentioning
confidence: 99%
“…Low-dose preincubation predominantly results in absolute tolerance, whereas high-dose preincubation induces both absolute and induction tolerance [289]. Amongst other mechanisms, the development of low-dose TNF tolerance as well as TNF-induced cross-tolerance towards LPS depends on the activity of GSK3 [286], since GSK3 remained in an active state during TNF preincubation [288], while pharmacological inhibition or genetic deletion of GSK3 are able to reverse the formation of these forms of tolerance [288,289]. Mechanistically, GSK3 inhibition appears to counteract several molecular effects observed in low-dose tolerized cells, especially the increased phosphorylation of NF-κB-p65 at the inhibiting site Ser468 and the reduced phosphorylation at the activating site Ser536 [289].…”
Section: Inhibition Of Gsk3 and The Perpetuation Of Inflammationmentioning
confidence: 99%
“…Interestingly, Park et al (72) examined TNF-␣-mediated induction of an endotoxin refractory state using exogenous TNF-␣ in the absence of primary LPS followed by a secondary LPS stimulation; TNF-␣ treatment inhibited NF-B signaling following LPS challenge and led to a tolerized state in human macrophages. TNF-mediated tolerance (termed "TNF tolerance") has been reviewed recently (73), and it has been suggested that TNF tolerance contributes to negative immune regulation similar to endotoxin tolerance. In our model, we observed differential TNF-␣ induction between THP-1 and PMA-THP-1 cells, where THP-1 cells exhibited less TNF-␣ induction compared with PMA-THP-1 cells.…”
Section: Il-27 Enhances Lps-tlr4-cd14 Signalingmentioning
confidence: 99%